Studi Fenomenologis tentang Pengalaman Kesepian dan Kesejahteraan Subjektif pada Janda Lanjut Usia - Sessiani, Lucky Ade (Sawwa: Jurnal Studi Gender, 2018)
Elderly women experience loneliness related to unexpected situations of partner loss (husband's death). Loneliness can have an impact on subjective well-being, life satisfaction, quality of life, mental and physical health, and even death. The purpose of this study was to describe and understand experiences related to loneliness for elderly widows. The subjects involved were 6 (six) widows due to the death of their husbands (widowed), widows of more than 1 year, and no history of psychological disorders. Methods of data collection using interviews and observation. This study resulted in the conclusion that an elderly widow can experience loneliness due to the loss of a spouse who is taken away by death. Subjective well-being and perceived life satisfaction are the results of a religious coping strategy that is effective in overcoming loneliness experienced. When feelings of losing a spouse can be overcome by religious behavior, enthusiasm for survival and re-establishing social interaction, the elderly can feel well-being and life satisfaction.